2022
DOI: 10.1002/app.52485
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide/thermoplastic polyurethane wrinkled foams with enhanced compression performance fabricated by dynamic supercritical CO2 foaming

Abstract: Thermoplastic polyurethane (TPU) foams are commonly used buffering materials due to their lightweight, high elasticity, and excellent energy absorption properties. Improving their compressive property without increase foam density is a challenge for TPU foams. Herein, graphene oxide (GO)/TPU composite foams containing micro‐sized wrinkles on the cell surface were fabricated by a novel dynamic supercritical carbon dioxide (scCO2) foaming method. The addition of GO created hydrogen bonding and physical crosslink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Besides, JPEs also exhibited advantages in the ability to enhance modulus with increasing density compared with conventional homogeneously modified strategies. As shown in Figure h, JPEs have a high value of B, which represents the ability to improve the modulus of porous materials with density and a high recovery compressive strain up to 70% superior to that of porous materials reported in the previous report. ,, Such superiority comes from the JP-armored interface, which could enhance the whole modulus of materials with minor sacrifices in density and elasticity by combining the soft matrix and hard interface.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Besides, JPEs also exhibited advantages in the ability to enhance modulus with increasing density compared with conventional homogeneously modified strategies. As shown in Figure h, JPEs have a high value of B, which represents the ability to improve the modulus of porous materials with density and a high recovery compressive strain up to 70% superior to that of porous materials reported in the previous report. ,, Such superiority comes from the JP-armored interface, which could enhance the whole modulus of materials with minor sacrifices in density and elasticity by combining the soft matrix and hard interface.…”
Section: Resultsmentioning
confidence: 70%
“…Referential data were extracted from ref (h) value of B representing the ability to enhance modulus by increasing the density and reported maximum strain during compression tests. Referential data were extracted from refs , , and .…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the uneven stress release in a polymer matrix or bilayer polymer film may cause the distortion of the surface layer and the formation of microwrinkles. , The rapid expansion and contraction of TPU during scCO 2 foaming is also capable of generating microsized wrinkles. , In dynamic scCO 2 foaming that involves a constant scCO 2 flow field, high-density fine wrinkles can be obtained in a one-step process . In this work, the wrinkled TPU surfaces were fabricated via dynamic scCO 2 foaming at varying scCO 2 flow rates (e.g., 18, 27, and 36 mL/min) (Figure S11).…”
Section: Resultsmentioning
confidence: 99%
“…27,84−86 In dynamic scCO 2 foaming that involves a constant scCO 2 flow field, high-density fine wrinkles can be obtained in a one-step process. 87 In this work, the wrinkled TPU surfaces were fabricated via dynamic scCO 2 foaming at varying scCO 2 flow rates (e.g., 18, 27, and 36 mL/min) (Figure S11). The wrinkled microstructure of different TPU surfaces is shown in Figure 9a−c, from which it is clear that the size of the wrinkles is gradually reduced, while the wrinkle density is increased with the increase of scCO 2 flow rates.…”
Section: Mechanism Of the Stress Release Induced Wrinklesmentioning
confidence: 99%
“…Closed-cell polymer foams, as a two-phase system that contains statistically distributed gasp bubbles Polymer foams, have been widely used as buffering materials because of their advantages of low density and efficient energy-absorbing properties. Most polymer foams absorb impact energy through plastic deformation or crushing, and they are unable to be reused due to permanent deformation. Yang et al investigated that bumper foam pads produce stress softening after multiple shocks, which reduces the energy absorption level of the foam . Landro et al have shown that high-density EPS can absorb more energy than low-density EPS, but will deliver a higher acceleration and force.…”
Section: Introductionmentioning
confidence: 99%